(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Forensic genetics has significantly reshaped the investigations’ methods and simultaneously brought numerous ethical and legal challenges, especially in the area of DNA data exchanges. By retracing the history of DNA cross-border exchanges within the so-called PrÃ¼m framework, this paper aims to underline not only the current inhomogeneity of Member States’ legislations in this complex field but also the existing inefficiencies in the implementation and application of the "PrÃ¼m system". On this basis, potential developments and possible reform solutions are analysed, with the purpose of explaining and reflecting on the opportunities and risks enshrined in the so-called Next Generation PrÃ¼m.